Status of human resource in the philosophy of Total Quality Management. - حدیدان , صبرینة (Finance and Business Economies Review, 2018)
Edward Deming called for a new philosophy of action based on valuing the human resource. This philosophy is a Total Quality Management, that depends on the success of the human resource to accept them. The aim of this research is to demonstrate the status of human resources in the philosophy of Total Quality Management, Based on the definition of its concept and theories, And to the importance of human resources to make it successful